Effect of Brand Image, Promotion and Physical Distribution on Brand Loyalty with Customer Satisfaction as the Intervening Variable - Muhamad Apep Mustofa; Nandan Limakrisna; Hari Muharam (Publikasi Indonesia, 2022)
This research is motivated by changes in the cement market in Indonesia along with the addition of several new cement brands that are competitors for the incumbent cement brands that have existed for a long time. Per capita cement consumption in Indonesia is still low compared to three ASEAN countries such as Malaysia, Vietnam and Thailand. Besides, there is a decrease in Top Brand Image between 2018-2019 for the Semen Tiga Roda brand. In the arena of increasingly fierce competition between brands, it is necessary to increase brand loyalty, where brand loyalty is influenced by the level of customer satisfaction. This customer satisfaction is an intervening variable to further increase brand loyalty. When customers are satisfied, they will be more loyal to the brand so that customers do not easily move to other brands. Many factors affect the increase in brand loyalty, including promotion, brand image and physical distribution. So the purpose of this study was to determine the effect of brand image, promotion and physical distribution on brand loyalty with satisfaction as an intervening variable. The location of the study was carried out in Greater Jakarta with the unit of analysis was members of the Greater Jakarta REI as many as 250 respondents. This research uses path analysis method with structural equation modeling (SEM) technique. These results find empirical facts that brand image, promotion and physical distribution together have a significant effect on customer satisfaction, and customer satisfaction has a significant effect on brand loyalty. Thus, the higher the customer satisfaction, the higher the brand loyalty will be.